Regulation of secretory pathway kinase or kinase-like proteins in human cancers - Du, Shaonan; Zhu, Chen; Ren, Xiaolin; Chen, Xin; Cui, Xiao; Guan, Shu (Frontiers in Immunology, 2023)
Secretory pathway kinase or kinase-like proteins (SPKKPs) are effective in the lumen of the endoplasmic reticulum (ER), Golgi apparatus (GA), and extracellular space. These proteins are involved in secretory signaling pathways and are distinctive from typical protein kinases. Various reports have shown that SPKKPs regulate the tumorigenesis and progression of human cancer via phosphorylation of various substrates, which is essential in physiological and pathological processes. Emerging evidence has revealed that the expression of SPKKPs in human cancers is regulated by multiple factors. This review summarizes the current understanding of the contribution of SPKKPs in tumorigenesis and the progression of immunity. With the epidemic trend of immunotherapy, targeting SPKKPs may be a novel approach to anti-cancer therapy. This study briefly discusses the recent advances regarding SPKKPs.